Stereotactic body radiotherapy for early-stage non-small cell lung cancer has low post-treatment mortality - Niska, Joshua R.; Sio, Terence T.; Daniels, Thomas B.; Beamer, Staci E.; Jaroszewski, Dawn E.; Ross, Helen J.; Paripati, Harshita R.; Schild, Steven E. (Journal of Thoracic Disease, 2018)
Stereotactic body radiotherapy (SBRT) is increasingly used to treat stage I non-small cell lung cancer (NSCLC). In 2004, less than 0.5% of these cases were managed with SBRT. By 2011, SBRT accounted for 8.7% of cases (1).